2022
DOI: 10.3390/covid2080083
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of COVID-19 Risk Perception and Its Correlates among University Students in Ghana

Abstract: Monitoring students’ risk perception forms part of emergency management during public health emergencies. Thus, public risk perception generally triggers attitudes, emotional responses, and prevention behaviors, which affect the evolution of emergencies and disease control strategies. However, research has paid less attention to the COVID-19 risk perception of students in Ghana. This study assessed the prevalence of COVID-19 risk perception and further identified its correlates among university students. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The DHL levels of COVID-19 among university students were also measured and compared for differences between students studying health-related and non-health-related programmes. The study findings indicate that a significant majority (60%) of the university students used a variety of digital platforms (73 to 94%) to search for COVID-19 information, such as search engines, social media, news portals, health portals, Wikipedia, websites of public institutions, YouTube, blogs on health, and websites of doctors or health insurance companies, which was also reported among medical students in Iran [48]. Similarly, studies in the USA [9], Portugal [10], Slovenia [11], China/Malaysia/Philippines [12], Saudi Arabia [13], and Vietnam [14] established that university students often used the internet, search engines (e.g., Google, Bing, Yahoo), Wikipedia, social media platforms (e.g., Facebook, Instagram, YouTube, Twitter), news portals (e.g., newspapers, TV stations), and websites of public bodies/official institutions to obtain information about COVID-19 during the pandemic.…”
Section: Discussionmentioning
confidence: 65%
“…The DHL levels of COVID-19 among university students were also measured and compared for differences between students studying health-related and non-health-related programmes. The study findings indicate that a significant majority (60%) of the university students used a variety of digital platforms (73 to 94%) to search for COVID-19 information, such as search engines, social media, news portals, health portals, Wikipedia, websites of public institutions, YouTube, blogs on health, and websites of doctors or health insurance companies, which was also reported among medical students in Iran [48]. Similarly, studies in the USA [9], Portugal [10], Slovenia [11], China/Malaysia/Philippines [12], Saudi Arabia [13], and Vietnam [14] established that university students often used the internet, search engines (e.g., Google, Bing, Yahoo), Wikipedia, social media platforms (e.g., Facebook, Instagram, YouTube, Twitter), news portals (e.g., newspapers, TV stations), and websites of public bodies/official institutions to obtain information about COVID-19 during the pandemic.…”
Section: Discussionmentioning
confidence: 65%
“…Remarkably, some studies have shown that students are motivated by the use of technology-driven platforms (such as Facebook, WhatsApp, YouTube, and Twitter) that offer direct gratification irrespective of the challenges associated with their usage ( Owusu-Ansah et al, 2021 ; Quansah et al, 2022 ). This observation suggests that students are likely to find means of overcoming the challenges associated with technology use when they are aware of any associated direct and/or indirect benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the convenience sampling strategy became necessary to use since the tensions around COVID-19 was still present and schools had just resumed after over 10 months of lockdown. The challenge was that several students were anxious and uncertain in terms participating in the study [ 5 ]. Hence, the researchers obtained 1,160 responses, although the target was to administer the questionnaire to 2,100 students which represents 5% of the population.…”
Section: Methodsmentioning
confidence: 99%